TRADITIONAL AUTHORITY IN SOUTH WAZIRISTAN TRIBAL DISTRICT: OPERATIONALIZATION OF MAX WEBER’S THEORY - Mohib ur Rehman (Journal of Peace, Development and Communication, 2022)
This research paper tends to operationalize Max Weber’s theory in the context of South Waziristan tribal district with special focus on one of its elements i.e., traditional authority. The study explains the Pashtunwali, a legitimized source in traditional authority, and its certain tenets like Tarburwali and Badal that lead to call for a Jirga; in which Malik, Khan, Mutabar and Speengery play an authoritative role. The study discusses many corelated topics such as hierarchical explanation of Pashtun tribes from the antecedent to South Waziristan’s tribes, comparative analysis of classic traditional structure of Pashtun to evolve and modern traditional structure with emphasis on South Waziristan, the cohesive nature of Pashtun tribal dynamics to resist against intruders, the function of Jirga as a Dispute Resolution Council (DRC), four types of Jirga with South Waziristan as a case study, reasons for structural destabilization in leadership, distinctive forms of Jirgas, its decision implementation procedure and punitive penalties measure in South Waziristan. The study is qualitative and data has been collected from both primary and secondary sources. A total of twenty respondents have been interviewed through purposive sampling with the help of unstructured/open-ended interviews.